Experimental analysis and simulation of a production line for CPV modules: impact of defects, misalignments, and binning of receivers. Issue 5 (30th October 2017) - Herrero, Rebeca; Antón, Ignacio; Victoria, Marta; Domínguez, César; Askins, Stephen; Sala, Gabriel; De Nardis, Davide; Araki, Kenji
Abstract: An inherent characteristic of high concentrator photovoltaics (HCPV) modules is a tight mechanical tolerance caused by the narrow angular transmission of the optical system, typically below or close to 1°. Misalignments in the modules caused during the assembly process in the production line will degrade not only the electrical but also the angular performance of the module. Moreover, dispersion in the electrical characteristics of the elementary units comprising a module would lead also to power loss. Quality control and data analysis on the production line is of great significance for adjusting the production line and preserving the angular tolerance and the electrical performance. This is particularly critical during the set‐up and tuning of an automated production line. This paper presents the results of a pilot production line for HCPV modules carried out within the European funded ECOSOLE project. Several quality controls were established, which are the binning of the photovoltaic receivers, the measurement of misalignments among the elementary units within every module, and the indoor electrical characterization of the modules. Collected experimental data during the tuning phase of the pilot line were used to validate a module performance model based on production parameters. Monte Carlo method is lately applied to the model to assess the influence of production defects of diverse nature and the adequacy of quality controls, in several manufacturing scenarios beyond the specific constrains of the ECOSOLE experience. Abstract : Collected experimental data during the quality control (e.g., the binning of the photovoltaic receivers, the measurement of misalignments among the elementary units within every module, and the indoor electrical characterization of the modules) of a production line for high concentrator photovoltaics (CPV) were used to validate a developed module performance model based on production parameters. Monte Carlo method is lately applied to the model to assess the influence of production defects of diverse nature, in several manufacturing scenarios.